Incidental Coronary Artery Calcium on Breast Radiation Therapy Planning Scans Identifies Patients for Cardiac Preventive Therapy. (November 2020) - Amin, Neha P.; Kim, Samuel M.; Lasio, Giovanni; Zhou, Jinghao; Romar, Linda; Shipman, Kalin; Dukes, Kelly; Amin, Nivee P.
Abstract : Purpose/Objective(s): The presence of coronary artery calcium (CAC>0) is associated with increased cardiac-related mortality and is a common indication to initiate statin therapy to prevent future long-term cardiac-related adverse events. CAC is also well visualized on noncontrast chest computed tomography simulation (CT sim) scans used for breast radiation planning. We hypothesize that by screening for incidental CAC on CT sims, radiation oncologists could help identify patients who may benefit from additional preventive medical interventions with their primary care physician or cardiologist. Methods: A retrospective analysis of 126 consecutive patients with breast cancer treated with external beam radiation therapy at a single institution was performed. Noncontrast CT sim scans were reviewed for the presence of CAC and the 10-year risk of atherosclerotic cardiovascular disease (ASCVD) was calculated to identify patients who may benefit from initiating statin therapy. Patients with CAC>0 and/or ASCVD risk >20% were identified as those who may benefit from statin therapy. Results: Out of 72 patients with CAC>0, only 12(16%) had reported pre-existing coronary artery disease and 32(44%) were not already on recommended statin therapy. CAC>0 visualized on CT sim was able to identify 29 additional patients who would benefit from statin beyond what the ASCVD risk calculator could identify. Conclusion: Observation of incidental CAC on breast radiation-planning CT scans identified patients who could benefit from cardiac-related preventive strategies. By increasing attention, awareness, and reporting of incidental CAC visible on CT sims, radiation oncologists may fulfill a unique role to bridge a potential gap in cardiovascular preventive medicine.